Structural and biochemical characterization of bees propolis - Rahim, Muhammad Kamil Abdul (2020)
Pharmacological and clinical evidence based related chemical studies to harness local folk or traditional medicines are predominantly initiated and were derived from exploitation of geo-located local ‘status quo’ flora and botanical plants biodiversity. As such this was the basis platform of most early medicines. Propolis is is the generic name of a natural resinous mixture produced by honey bees from substances collected from parts of plants, buds, and exudatesin different geographic areas. Propolis honeybee product have been used in global traditional folk medicine signatures for antioxidant, immune-stimulating, anti-inflammatory and anti-cancer effects. While in the industrial era, propolis application in health care has become more trending but much evidence base extrapolation still need to be explore. For acknowledgement, the paradigm concerning propolis chemistry radically changed. There are very few studies that characterize the content of Trigona spp and comparison with Apis mellifera propolis in terms of the nature of the propolis, the compound present, the safety issue and also the stability of the substances in formulation product. In this research, semi-quantitative and qualitative approaches had been used to characterize Trigona spp and Apis mellifera propolis. Trigona spp propolis was collected from Kubang Kerian, Kelantan in June 2011 and was characterized using HPTLC, GC-MS, SEM surface analysis and EDX microanalysis to determine the chemical properties and compounds present in the sample. HPTLC result showed 7 types of phenolic compounds with 3 antixodiant compounds present in Trigona spp propolis while 3 antioxidant compounds in Apis mellifera propolis. The compounds currently unidentified as the banding showed no similarities with standards used in this study (Caffeic acid, Naringenin, Naringin, Kaempferol and Luteolin). The GC- MS data detected 2 types of volatile phenolic compound (Cardol in both propolis, Cardanol in Trigona spp and1,3-Benzenediol,5-pentadecyl in Apis mellifera propolis). The in vitro evaluation showed Trigona spp contained higher phenolics compound with almost similar level of antioxidant capactiy compared to Apis mellifera propolis. Ultra-microscopy data showed presence of majority flat layer homogenized layer in both propolis where Trigona spp propolis showed more presence of compounds. Presence of more pollen, seed-like structure and microfibre wooden chip in Trigona spp propolis support chemical finding of different foraging behavior compared to Apis mellifera. Trigona spp and Apis mellifera propolis obtained in Malaysia contain phenolic compounds similar to propolis reported in Thailand and Indonesia. The propolis did not contain well known phenolic compounds commonly seen in the European country. It also contained several trace elements, and free from volatile toxic compound